The Influence of Literacy Skills on Improving Students Reading Interest in Indonesia Language Learning: A Quantitative Studi of 5th Grade Elementary Students - Nasution, Nirwansyah; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study examines the influence of literacy skills on the improvement of reading interest among fifth-grade students in Indonesian language learning at SD Negeri 135 Barbaran. The background indicates that students' literacy skills still need improvement. Initial observations and interviews with fifth-grade teachers confirmed low student reading interest due to a lack of reading habits outside lessons, exposure to monotonous reading materials, and limited facilities. Therefore, this research aims to provide concrete solutions through curriculum-integrated literacy development. A quantitative approach with an ex post facto method was employed. The study population comprised all 34 fifth-grade students of SD Negeri 135 Barbaran, who were included as a full sample using purposive sampling. Data were collected through questionnaires (reading interest) and tests (literacy skills). The instruments were validated (r-count > 0.3494) and reliable (Cronbach's Alpha 0.952). Data analysis included descriptive statistics, classical assumption tests (normality Sig. 0.200 ≥ 0.05; linearity Sig. 0.367 ≥ 0.05), and simple linear regression hypothesis testing. Descriptive data showed that students' literacy skills were predominantly in the